2012
DOI: 10.1016/j.cell.2012.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Architecture of the Rod Sensory Cilium and Its Disruption in Retinal Neurodegeneration

Abstract: Summary Defects in primary cilia lead to devastating disease due to their roles in sensation and developmental signaling, but much is unknown about ciliary structure and mechanisms of their formation and maintenance. We used cryo-electron tomography to obtain three-dimensional maps of the connecting cilium and adjacent cellular structures of a modified primary cilium, the rod outer segment, from wildtype and genetically defective mice. The results reveal the molecular architecture of the cilium and provide ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
218
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(234 citation statements)
references
References 51 publications
14
218
2
Order By: Relevance
“…An insufficient supply of Stx3 and Stxbp1 in the IS may result in a delay or failure of vesicle fusion at the IS/OS interface. Although we were not able to quantify it in our micrographs, accumulation of vesicles was observed near the base of connecting cilium of Bbs4 mutant photoreceptors (38). This phenotype could be a result of the deficiency of Stx3 and Stxbp1 in the IS.…”
Section: Discussionmentioning
confidence: 60%
“…An insufficient supply of Stx3 and Stxbp1 in the IS may result in a delay or failure of vesicle fusion at the IS/OS interface. Although we were not able to quantify it in our micrographs, accumulation of vesicles was observed near the base of connecting cilium of Bbs4 mutant photoreceptors (38). This phenotype could be a result of the deficiency of Stx3 and Stxbp1 in the IS.…”
Section: Discussionmentioning
confidence: 60%
“…Our tomographic reconstructions also show that successive ciliary plasma membrane evaginations fuse to form discrete discs. This progressive disk closure from the axoneme could lead to the nascent discs appearing to be enclosed by plasma membrane, as previously described in both frozen and chemically fixed preparations (13,15), depending upon the position of the axoneme within the section plane and the section orientation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the existence of rhodopsin-bearing vesicles and tubules within the connecting cilium and at the base of the OS (13), but others have reported that most rhodopsin is transported on the ciliary plasma membrane (14). Furthermore, cryoelectron tomography failed to identify vesicles within the connecting cilium, but also presented data suggesting that nascent discs were enclosed within plasma membrane, which cannot be fully explained by either model (15).In this manuscript, we show by immuno-EM that rhodopsin is transported primarily on the ciliary plasma membrane. By conventional EM and tomography, we demonstrate fusion of the open ends of adjacent nascent OS discs that have been formed by evaginations of the ciliary plasma membrane.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In photoreceptors, the sensory cilium forms a narrow isthmus that connects the metabolically active inner segment (IS) to the outer segment (OS). Membrane and soluble proteins essential for phototransduction and critical for maintenance of the OS traffic through the photoreceptor cilium (6,7).…”
Section: Introductionmentioning
confidence: 99%